Faktor-faktor yang Mempengaruhi Penggunaan dan Penerimaan Jaringan 5G: Aplikasi Model UTAUT - Ummi Ainun Nadhiroh; Erma Suryani (EXPERT: Jurnal Manajemen Sistem Informasi dan Teknologi, 2023)
Factors Affecting the Use and Acceptance of 5G Networks: UTAUT Model Applications - Internet technology never stops making the development of the digital era enter the 5G technology stage. However, the market for 5G technology is still relatively small in Indonesia due to several factors, one of which is the uneven demand for communication technology in Indonesia. Thus, the purpose of this study is to analyze the behavior of internet users toward the 5G network by looking at what factors influence the community towards using the 5G network as a UTAUT approach. In analyzing the data, researchers used the SEM-GSCA method with 202 samples of 5G users in Indonesia. This study concludes that there are significant factors that influence people's interest in using the 5G network, including performance expectancy, effort expectancy, and facilitating condition variables, while the social influence variable does not have a significant effect on interest in using the 5G network. In addition, it was found that there was a significant influence between the intention to use the 5G network and the intention to buy a subscription to the 5G network.